Development of Smart Board Pakapin Media in Science Learning Class V Elementary School - Ramadhani Syafitri Siregar; Sukmawarti Sukmawarti (Edumaspul: Jurnal Pendidikan, 2022)
This research is Research and Development (R&D) research using 3 stages of the ADDIE model, namely analysis, design, and development. The subjects of this study were 25 students in class V SD Negeri 060924 Medan for the academic year 2022/2023. The final product of this development is the smart pocket board media. The development of Pakapin media was validated by 3 validators, namely media expert validation, material expert validation and learning expert validation. The results of this study prove that the validity level of smart pocket board media shows an average percentage of media experts 92.5%, material experts 86%, and learning experts 100%, which means that smart pocket board media is categorized as very valid. This shows that Pakapin media can improve student learning outcomes.